Caring, sharing, preparing and declaring: how do hospices support prisons to provide palliative and end of life care? A qualitative descriptive study using telephone interviews - McParland, Chris (Palliat Med, 2020)
BACKGROUND: Older adults in prison have complex healthcare needs, and many will need palliative care before their sentence ends. Compared with prison-based hospices, little is known about the role played by community-based hospices in providing palliative care to people in prison AIM: To describe the roles Scottish hospices have adopted to support prisons to provide palliative care, and to discuss the international relevance of these findings in addressing the knowledge gap around community hospices supporting people in prison. DESIGN: A qualitative descriptive study using semi-structured telephone interviews. SETTING/PARTICIPANTS: Representatives from all Scottish adult hospices were invited to take part in a short telephone interview and all (N = 17) participated. RESULTS: Four roles were identified: caring, sharing, preparing and declaring. Most hospices employed different combinations of roles. Five (30%) hospices were engaged in caring (providing direct care at the prison or the hospice). Eleven (65%) hospices were engaged in sharing (supporting the prison by sharing knowledge and expertise). Eleven (65%) hospices were engaged in preparing (making preparations to support prisons). All seventeen hospices were described as declaring (expressing a willingness to engage with prisons to provide care). CONCLUSIONS: There are differences and similarities in the way countries provide palliative care to people in prison: many are similar to Scotland in that they do not operate prison-based hospices. Variations exist in the level of support hospices provide. Ensuring that all people in prison have equitable access to palliative care will require close collaboration between prisons and hospices on a national level.